The effect of internal and information integration on Oman container ports? operational performance: The mediating role of supply chain management practices - Al Azzani A.; Isa A.A.M.; Mahdi O.; Khudari M. (EnPress Publisher, LLC, 2025)
This study aims to investigate the relationship between internal and information integration within the supply chain (SCI-INTI and SCI-INFI), supply chain management (SCM) practices, and port operational performance (POP) in Oman?s container ports. Additionally, it explores the mediating role of SCM practices in the relationship between SCI-INTI, SCI-INFI, and POP in Oman. To meet the study?s objectives, a quantitative cross-sectional survey method was used. A total of 377 questionnaires were distributed to managers responsible for supply chain operations in the main departments at Sohar and Salalah ports, yielding 331 usable responses, with a response rate of 88 percent. The data collected were analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that both internal and information integration within the supply chain have positive and statistically significant effects on the operational performance of Oman?s container ports (POP). Specifically, Supply Chain Integration with Internal Integration (SCI-INTI) significantly impacts POP (? = 0.249, t = 5.039, p < 0.001), and Supply Chain Integration with Information Integration (SCI-INFI) also significantly affects POP (? = 0.259, t = 4.966, p < 0.001). Additionally, SCI-INTI positively influences Supply Chain Management Practices (SCMP) (? = 0.381, t = 7.674, p < 0.001), as does SCI-INFI (? = 0.484, t = 9.878, p < 0.001). Furthermore, SCMP positively and significantly influences the operational performance of Oman?s container ports (? = 0.424, t = 7.643, p < 0.001). These findings contribute to the literature by emphasizing the significance of internal and information integration within the supply chain and SCM practices as strategic internal resources and capabilities that enhance operational performance in container ports. Understanding these elements enables decision-makers and policymakers within government port authorities and port operating companies to optimize internal resources and capabilities to improve port operational performance. ? 2024 by author(s).